Impact of Perceived Role of Ethics and Social Responsibility on Ethical Evaluation of Earnings Management and Motivation to Use It - Striupaitytė, Milda; Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2023)
In this paper, earnings management is analyzed in the light of stakeholder theory in order to evaluate earnings management ethics. The main reasons for using earnings management are studied and systematically arranged in the context of stakeholder theory. An assumption is made that together with other motives mentioned in the literature, perceived role of ethics and social responsibility may not only influence ethical evaluation of earnings management, but also impact use of earnings management in accounting practice. The results of a study on impact of perceived roles of ethics and social responsibility on ethical evaluation of earnings management, carried out among accountants providing professional services in Lithuania, are presented in this paper. The ethical evaluation of earnings management has been found to depend on its type. Accrual-based earnings management is seen as more unethical than real earnings management. It also reveals that accountants’ belief that business ethics and social responsibility are less important is a motivation for the use of manipulative accounting.